The Effect of Financial Literacy on Entrepreneurial Intention with Self-Efficacy as a Moderator - Khaerunnisah. A; Ahmadi Usman; Syahriah Sari (Jurusan Administrasi Niaga, Politeknik Negeri Ujung Pandang, 2025)
Entrepreneurship is considered a strategic solution to reduce unemployment among graduates, yet many students still lack the confidence and financial knowledge needed to start a business. This research addresses the gap by examining the influence of financial literacy on entrepreneurial interest, moderated by self-efficacy, among students of the Business Administration Department at Politeknik Negeri Ujung Pandang. The study employed a quantitative method with data collected through questionnaires distributed to 168 students. The analysis was conducted using Moderated Regression Analysis (MRA) via IBM SPSS Statistics 25. The findings showed that financial literacy had a positive effect on students’ entrepreneurial interest. Among the financial literacy indicators, financial attitude scored the highest, while financial knowledge was the lowest. Self-efficacy was also found to be high, with generality as the strongest indicator. Additionally, self-efficacy strengthens the relationship between financial literacy and entrepreneurial interest. These results suggest the importance of improving both financial understanding and confidence in one’s entrepreneurial abilities. Institutions are encouraged to integrate more practical and reflective learning strategies in entrepreneurship and finance courses to boost students’ readiness to start their own ventures.